2010
DOI: 10.1007/s00253-010-2625-0
|View full text |Cite
|
Sign up to set email alerts
|

Combination of the 2A/furin technology with an animal component free cell line development platform process

Abstract: The recently described 2A/furin technology combines both chains of the antibody in a single open reading frame. Upon translation and secretion, the peptide is processed by the cell to generate native fully functional IgG antibodies. Here, we describe the results of an evaluation study of this technology for an industrial CHO cell line development process. The 2A/furin expression cassette setup was combined with a Novartis vector system. A transfection, selection, and cloning procedure in chemically defined med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 17 publications
0
24
1
Order By: Relevance
“…Transfection of CHO K1PD cells and selection/amplification with G418 and methotrexate were performed as previously described (Jostock et al, 2010).…”
Section: Generation Of Stable Cho Pools Expressing Canine Chimeric Anmentioning
confidence: 99%
“…Transfection of CHO K1PD cells and selection/amplification with G418 and methotrexate were performed as previously described (Jostock et al, 2010).…”
Section: Generation Of Stable Cho Pools Expressing Canine Chimeric Anmentioning
confidence: 99%
“…21,28 Productivities of F2A vector derived clones have been shown to be comparable to those generated using an industry reference vector designed to use separate expression units for each gene. 29 Studies had also shown that using F2A gave over 2-fold higher mAb expression levels than IRES in transient transfections and 20% higher expression in stable transfection. 18,21 However, incomplete cleavage of F2A was observed in some studies, resulting in HC-F2A-LC or LC-F2A-HC fusion proteins and LC and HC attached with F2A remnants.…”
Section: Introductionmentioning
confidence: 99%
“…26 F2A from the foot-andmouth disease virus, which is the most studied 2A, has been used for mAb expression in mammalian cells and for in vivo gene therapy. 18,21,[27][28][29][30][31] 2A peptides have approximately 20 amino acids and "self-cleavage" occurs between the last 2 amino acids, glycine (G) and proline (P). Adding a furin recognition sequence between the first gene and 2A aids in removing 2A residues from the upstream gene.…”
Section: Introductionmentioning
confidence: 99%
“…21 Using combination of furin recognition site and 2A-peptide strategy of expression has shown stable co-expression of transgene in different cell lines. 22 Although the 2A system is appropriate for delivering co-expression of particular sets of transgenes, it is not suited in situations where individual transgenes require a different tissue distribution. 23 Our studies of immunogenic properties of obtained adenoviral construction demonstrated low immunogenicity of 2A peptide sequences when utilizing furin cleavage.…”
Section: Discussionmentioning
confidence: 99%